2021
DOI: 10.1177/1177180121996063
|View full text |Cite
|
Sign up to set email alerts
|

The use of realist approaches for health research in Indigenous communities

Abstract: Research approaches and underlying epistemologies should be carefully considered when conducting health research involving Indigenous communities in order to be aligned with the distinct Indigenous values and goals of the communities involved. If Western research approaches are used, it is helpful to consider how they might be consistent with Indigenous ways of knowing. Among Western research approaches, realist approaches might have some congruence with Indigenous epistemologies. For health research in Indige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“… 55–57 Studies have shown that RE is relevant for health research with Indigenous communities because it is based on a holistic approach congruent with Indigenous ontologies. 58 …”
Section: Methodology and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“… 55–57 Studies have shown that RE is relevant for health research with Indigenous communities because it is based on a holistic approach congruent with Indigenous ontologies. 58 …”
Section: Methodology and Analysismentioning
confidence: 99%
“…RE, a theory-based approach to evaluation, is also recommended for evaluating complex situations, as it makes it possible to relate the context and underlying mechanisms that can influence the effectiveness of a process in a given setting 55–57. Studies have shown that RE is relevant for health research with Indigenous communities because it is based on a holistic approach congruent with Indigenous ontologies 58…”
Section: Methodology and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A method that advocates for the use of multiple data collection methods (34) , realist evaluation is a theory-driven approach that allows for a more in-depth understanding of an intervention or phenomenon by identifying different patterns (35,36) . It is an approach that is rooted in local knowledge (37) , process-oriented (37,38) , and able to link different knowledge systems together (37) , and it could be used more often in contexts such as Latin America (39) to address nursing research priorities.…”
Section: How To Respond To Identified Nursing Research Prioritiesmentioning
confidence: 99%
“…Guidance for the design and facilitation of realist interviews is readily available (Greenhalgh et al, 2017; Manzano, 2016; Mukumbang et al, 2019; Pawson, 1996; Pawson & Tilley, 1997; Westhorp & Manzano, 2017), but to date, it has given little attention to interviewing in cross-cultural contexts (when researcher and research participant are from different cultures and speak different languages). While some researchers have considered cross-cultural issues such as realist methodology’s compatibility with Indigenous ways of knowing (Bergeron et al, 2021), published realist evaluation studies that have included cross-cultural interviews are few (Gilmore, 2019), and give light descriptions or analyses in relation to the cross-cultural application of realist methodology.…”
Section: Introductionmentioning
confidence: 99%